شاہ عبد العزیزمحدث دہلویؒ - علمی و اصلاحی خدمات (ایک تجزیاتی مطالعہ): Scholarly and Reforms Services of Shah Abdul Aziz Muhaddith Dehlavi: Analytical Study - Dr. Mohammad Shamim Akhter, (MEI, 2022)
When light of Islam appears on the land of Sub-Continent, it started spreading day by day due to its pious teachings. Moreover, religious scholars, Sufis, and owners of the shrines (Gaddi Nasheen) take their part to spread Islam. However, Emperor, Kings of Temari Sultanate, Ministers, or Members of that specific Kingdome did not take any part in this scenario. Although, they did not forbid these kind people to do so. These people came in front whenever any social evil took birth and tried to highlight those issues that they cannot ignore their responsibilities as the leaders of the Muslim. Sheikh Ahmed Sarhandi’s (1544-1624) efforts to stop wrongs act in Akbar’s era are the outshine examples in this regard. Shah Waliullah Muhaddis Dehlvi tried to stable the Mughal empire and made plan but couldn’t succeeded. After him, Shah Abdul Aziz Dehlvi spend his whole life along with his scholarly and educational abilities to develop a path to restitute gone dignity and to make Muslim society a model society. This article is a study to focus on Shah Abdul Aziz’s those efforts.